PENGARUH TINGKAT INDEPENDENSI, KOMPETENSI, OBYEKTIFITAS, DAN INTEGRITAS AUDITOR TERHADAP KUALITAS AUDIT YANG DIHASILKAN KANTOR AKUNTAN PUBLIK DI SURABAYA - LIE DAVID GUNAWAN (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Company's and the auditors profession alike are faced with severe challenges. They both have to maintain our existence in competition with the company's competitors or associates seprofesinya. The company wants unqualified opinion as a result of the audit report, in order peformanya look good in the public eye so it can run its operations smoothly. Variables used in this study were independent variables: independence, competence, objectivity, integrity and the dependent variable is the quality of audits. This study aims to analyze the influence of the independence, competence, objectivity, integrity of audit quality produced by the auditor in Surabaya. The research data obtained from questionnaires by the number of data by 35 respondents. These results indicate that the independence, competence, objectivity, integrity significant effect on audit quality. From these results: independence, competence, objectivity, integrity as a concern for the auditor in Surabaya to produce a good quality audit.